Corporate Social Responsibility (CSR) and Deposit Money Bank’s Financial Performance - Adu, Cecilia Adurayemi; Ajigbotoso, Moses Ade (Indonesian Journal of Banking and Financial Technology, 2024)
The study examined the effect of corporate social responsibility on the financial performance of deposit money banks in Nigeria. Primary data were adopted for this study through the administration of some copies of questionnaire. The OLS regression was used to analyse the data and it was found out that the there is a positive significant relationship between Corporate Social Responsibility and the return on assets of commercial banks in Nigeria. It was suggested that the deposit money banks should ensure they embark on more structured and well planned Corporate Social Responsibility.